Di-(2-Ethylhexyl) Phthalate Exposure Is Negatively Correlated with Trait Anxiety in Girls but not with Trait Anxiety in Boys or Anxiety-Like Behavior in Male Mice. (January 2015) - Park, Subin; Cheong, Jae Hoon; Cho, Soo-Churl; Kim, Jae-Won; Shin, Min-Sup; Yoo, Hee Jeong; Han, Doug Hyun; Kim, Bung-Nyun
The authors aimed to study the effects of postnatal exposure to phthalate on anxiety-like behavior in mice and anxiety proneness in children. Male Imprinting Control Region (ICR) mice aged 4 weeks were administered 20 to 540 mg/kg of di-(2-ethylhexyl) phthalate (DEHP) or vehicle and assessed in the Open Field Test. A group of 277 children aged 8-11 years (150 males) was recruited from South Korea. A cross-sectional examination of urinary DEHP and dibutylphthalate metabolite concentrations was conducted, and the children were scored on the Trait Anxiety Inventory for Children (TAIC). DEHP metabolite concentrations in the urine were significantly and negatively correlated with TAIC scores in the female population but not in the male population. There were no significant group differences in the percentage of distance moved or time spent in the central area in male mice treated with DEHP or vehicle. Our results suggest a sex-dependent effect of DEHP on anxiety proneness in childhood.